PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL DRILLING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III B SD NEGERI 11 KERINCI KIRI KECAMATAN KERINCI KANAN - Oktarina, Sari; Marhadi, Hendri; Lazim.N, Lazim.N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of the problem in this research was the poor students’ achievements in social sciences , it can be seen on students’ social sciences scores. There were 12 of 19 students who had not achieved the achievement standard (63%), while the ones who achieved wer only 7 students (37%) and the average scores of the class was 55,68. The achievement standard that school determines in 65. The method of research was classroom action research implemented in two cycles that consist of planning, action, observation and reflection. At the first meeting in cycle I, the percentage of teachers’ activity was 67,5% which is categorized as good. At the second meeting, the percentage increased to 72,5% which is categorized as good. At first meeting of cycle II, the percentage increased to 75% that is categorized as very good. At second meeting, the percentage increased to 77,5% which is categorized as very good. The students’activities has increased. At first meeting in cycle I, the students’ activities gained 65% which is categorized as good, while at second meeting in cycle I, the students’ activities gained 67,5% which is categorized as good. At the first meeting of cycle II, the percentage increased to 75% that is categorized as very good, while the second meeting the percentage increased to 77,5% which is categorized as very good. The average of students’ achievements before the implementation cooperative learning snowball drilling type was 55,68, which incerased 76,84 in cycle I and increased again 83,16 in cycle II. The result of research showed that implementation cooperative learning snowball drilling type can improve students result of social sciences of grade three B at SDN 11 Kerinci Kiri Kecamatan Kerinci Kanan.Key Words: Study Result, Cooperative Learning Snowball Drilling Type, Social Sciences